2021
DOI: 10.4070/kcj.2021.0995
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification in Chronic Kidney Disease: Distinct Features of Pathogenesis and Clinical Implication

Abstract: Author's summary Vascular calcification (VC) is highly prevalent in patients with chronic kidney disease (CKD) and leads to increased cardiovascular morbidity and mortality. In patients with CKD, traditional factors do not fully explain the high prevalence of VC. This suggests that a CKD-specific pathobiology is involved in the development of VC and mounting evidence indicates that VC in CKD patients has distinct features of clinical presentation and that clinical implications are changed compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 176 publications
(183 reference statements)
0
14
0
Order By: Relevance
“… 3) Male gender, white race, metabolic syndrome, uremia and diabetes mellitus all increase risk of coronary calcification. 4) 5) 6) 7) …”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
“… 3) Male gender, white race, metabolic syndrome, uremia and diabetes mellitus all increase risk of coronary calcification. 4) 5) 6) 7) …”
Section: Epidemiology and Outcomesmentioning
confidence: 99%
“…The α-klotho protein functions as a co-receptor or scaffold protein for the fibroblast growth factor (FGF) receptor (FGFR). Binding of FGF23 produced in bone to the renal FGFR regulates phosphate reabsorption and calcitriol production in the kidney; therefore impaired FGF23 activity due to reduced α-klotho expression leads to dysregulation of phosphate and vitamin D homeostasis thereby contributing to vascular calcification [ 26 ]. Phosphatemia is also associated with increased ROS and free radicals, which can inhibit endothelial NO synthase (NOS) activity to reduce NO productionand increase peroxynitrite (ONOO – ) generation [ 27 ].…”
Section: Vascular Injurymentioning
confidence: 99%
“…Prior studies have shown that both traditional and non-traditional risk factors are multifactorial in the pathogenesis of CVD in patients with ESRD. Moreover, it is difficult to predict the occurrence of cardiovascular (CV) events in these patients [ 2 ]. ESRD patients with CVD often show no or atypical symptoms, resulting in delayed diagnosis and failure to receive appropriate management of CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ESRD have a high prevalence of vascular calcification, which shows distinct pathophysiological features compared to those in the general population [ 2 , 10 ]. Patients with ESRD undergoing HD are at risk of atherosclerotic injury because they are constantly exposed to endothelial injury, oxidative stress, and inflammation.…”
Section: Introductionmentioning
confidence: 99%